Mechanical properties of chicken feather fibre reinforced epoxy composites - F. B. H., Nurul; Abdul Hanan, Umar; Salit, Mohd Sapuan (2009)
The objective of this research is to study mechanical properties of chicken feather fibre reinforced epoxy (CFFRE) composites especially tensile and flexural properties. The composites were fabricated using random orientation lamination with similar fibre volume fraction (10%) through hand lay-up method but with different types of raw material processes. First and foremost, the chicken feathers undergo two processes which are processed by using hot water and also without hot water. These processes affect the density of chicken feathers. For each of type, five specimens were prepared and tested for both tensile and flexural testing according to ASTM D638-99 and ASTM D790-97 standards, respectively. For the CFFRE composites which the fibre processed by using hot water showed the tensile Young’s Modulus is 1062.5 MPa, tensile strength is 10.0 MPa, the flexural modulus of elasticity is 3950.9 MPa and 77.9 MPa for the flexural stress. Meanwhile, for the CFFRE composites which the fibre processed without using hot water showed the tensile Young’s Modulus is equal to 1062.2 MPa, tensile strength is 11.2 MPa, the flexural modulus of elasticity is 1814.4 MPa, and flexural strength is 48.6MPa. Thus, the chicken fibre loading was not possible by using the hand lay-up method. This is because chicken feather fibres have intrafibre voids called lumen which influenced the presence of entrapped air bubbles. Epoxy was not the appropriate matrix resin to be use with chicken feather fibre. Other factors such as the interaction of fibre towards matrix, multidirectional orientation of the fibre, lower fibre content, type of fabrication process, moisture content and the pretreatment of fibre affect the mechanical properties of the composites.